A study on driving behavior characteristics and influencing factors of older drivers at signal-controlled and unsignal-controlled intersections - Yang Li; Bingshuo Chen; XiaoHua Zhao; Hongzhen Zhu; Wei Guo; Wei Han (PLoS ONE, 2025)
Due to a decline in psychological function, older drivers have a high incidence of crashes, especially at intersections. The study considered the characteristics of older drivers and designed a driving experiment that includes two scenarios: signal-controlled intersections and unsignal-controlled intersections. A total of 39 drivers participated in the experiment. The results indicated that compared to the young and middle-aged drivers, older drivers exhibited the following characteristics. From a time perspective, older drivers initiated decelerate and turning maneuvers earlier after entering intersections. Their overall turning process was smoother, as indicated by smaller peak steering wheel cornerings, lower steering reversal rates, and reduced lateral acceleration variability. And older drivers slowed down and turned earlier at signal-controlled intersections. From a spatial perspective, older drivers experienced a decrease in speed before entering the two intersections, followed by a sustained increase in speed and steering wheel cornerings. And there were frequent fluctuations in the speed and steering wheel cornering of older drivers at unsignal-controlled intersections. Finally, two Generalized Linear Mixed Models were developed to examine factors affecting driving stability, focusing on speed and steering control. Results showed that traffic control, driver type, and cognitive function had significant impacts. These findings enhance understanding of older drivers’ behavior and provide a reference for improving age-friendly transport systems and safety training. To better support older drivers, vehicle design, traffic signs, infrastructure planning, and management policies should consider their driving characteristics.